Pemanfaatan Reading Corner dalam Meningkatkan Kemampuan Literasi Membaca Peserta Didik di Sekolah Dasar - Lilis Amaliah Rosdiana; Dewi Kusuma (Universitas Suryakanca, 2025)
This article aims to examine the implementation of reading corners in elementary schools and their impact on increasing literacy skills. The method used is a Systematic Literature Review (SLR) by analyzing twelve relevant scientific articles published in the last five years. The review process was conducted thru five stages: problem identification, setting inclusion and exclusion criteria, searching for articles using the keywords